Proposing a Comprehensive Model to Explore and Evaluate the Factors Influencing Egyptian Consumers’ Brand Loyalty: An Empirical Study in the Home Appliances Sector - Shalash, Mostafa Ahmed (British Journal of Marketing Studies, 2025)
The home appliance industry in the Egyptian market is currently witnessing rapid growth with very intense competition. In light of this fierce competition, the concept of brand loyalty has emerged as an important issue that should be carefully studied. Although manufacturers realize the importance of this concept, there is still no agreement on the factors that influence it. Furthermore, a lot of previous studies have examined the role of mediator variables in generating brand loyalty and conceptualized these mediating variables as a necessary commitment. However, there may be no need for such intermediary factors, rather the relationship can be direct between the antecedents of brand loyalty and brand loyalty. As such, this study aims to (1) develop an integrated conceptual model to discover the factors that Egyptian consumers rely on to build their loyalty in the context of home appliances, and (2) detect the relative importance of each factor in achieving overall consumer brand loyalty. To fulfill these objectives, the study proposes six factors namely brand trust, brand image, after-sales service, customer satisfaction, perceived quality, and brand experience. The novelty in this study lies in proposing one integrated model that includes the main determinants responsible for brand loyalty and studying them together instead of studying the influence of each determinant separately as in previous studies. In addition, till now there is no clear insight into whether the proposed factors have a direct or mediating effect on brand loyalty; this research attempts to answer this controversial question. For this purpose, the survey method is used as the primary data collection. 400 questionnaires were randomly distributed to home appliance buyers living in Alexandria city. The collected data were analyzed statistically using SPSS software. Correlation analysis, multiple linear regression, and stepwise regression were used to reach our results. The main findings of the study indicated that there is a significant and direct relationship between all proposed factors and consumer brand loyalty. However, after-sales service, perceived quality, brand trust, and customer satisfaction are notable determinants and have the highest relative importance on Egyptian consumer brand loyalty concerning home appliances.